More satisfied, but why? A pooled patient‐level analysis of treatment satisfaction following the initiation of insulin glargine vs. comparators in insulin‐naïve patients with type 2 diabetes mellitus. Issue 3 (16th October 2013) - Polonsky, W.; Traylor, L.; Wei, W.; Shi, R.; Ameer, B.; Vlajnic, A.; Nicolucci, A.
<x xml:space="preserve">Abstract</x> Aim To assess patient‐reported outcomes associated with initiating insulin glargine among insulin‐naïve patients with type 2 diabetes mellitus (T2DM). Methods This was a pooled analysis of patient‐level data from Phase 3, randomized controlled trials evaluating once‐daily insulin glargine vs. comparator treatment for ≥24 weeks in previously insulin‐naïve adult patients with T2DM and poor glycaemic control. Eligible studies utilized strict, predefined insulin titration algorithms with weekly dose‐adjustment to achieve fasting plasma glucose (FPG) levels of ≤5.6 mmol/l. Treatment satisfaction was measured using the Diabetes Treatment Satisfaction Questionnaire (DTSQ) change (c) and status (s) versions. Results A total of 1577 patients from four studies were included; 830 patients treated with insulin glargine and 747 with comparators. At week 24, DTSQc scores improved in both groups with a significantly higher increase in treatment satisfaction for insulin glargine vs. comparators (13.5 vs. 12.1; p < 0.0001). Multivariate regression analysis revealed that significant predictors of DTSQc improvement at week 24 were insulin glargine treatment (p < 0.0001), higher baseline DTSQs (p < 0.0001), and lower baseline body weight (p = 0.0103). Greater improvement in DTSQc at week 24 was significantly associated with decrease from baseline in glycosylated haemoglobin (p < 0.001) and FPG (p = 0.0001); a numerically more positive change in weight from baseline approached significance (p = 0.07). Conclusion Initiation of insulin glargine in insulin‐naïve patients with T2DM is associated with greater improvements in treatment satisfaction than alternative interventions, with perceived improvements in glycaemic control and baseline weight likely to be important factors.